A hopeful harvest [large type] - Herne, Ruth Logan (Love inspired., 2019)
"When her family's apple orchard is damaged by a storm, single mom Libby Creighton knows the harvest she's depending on is in jeopardy. Though he prefers a solitary life, Jax McClaren has the skills to revive Libby's orchard--and her guarded heart. But he'll have to overcome the secrets of his past if he and Libby are going to have a fruitful future together"--Back cover.